Domain Decomposition Algorithms for Edge Element Based Parabolic Type Problems - Marcsa, D. (Acta Technica Jaurinensis, 2014)
Today, a huge amount of interest in new actuators and a correspondingly huge pressure on companies and research centers to develop the most efficient, cost-effective electric design of the actuators for electric vehicles. However, the design and analysis of actuators is very complex task, thus need the help of multiprocessor computers to run efficient computations. This work analyzes the use of two non-overlapping domain decomposition methods (DDMs) in order to improve the calculation behaviour of finite element method (FEM) with edge element approximation. In this case, the DDMs under investigation are the Schur complement method and the Lagrange multiplier based Finite Element Tearing and Interconnecting (FETI) method with their algorithms. The performance of these methods and solvers have been investigated in detail for two-dimensional parabolic type problems as case studies.